Website Defacement and Routine Activities: Considering the Importance of Hackers’ Valuations of Potential Targets - Burruss, George W. (2019)
Although a relatively simple form of hacking, website defacement can have severe consequences both for the websites that are attacked and the reputation of their owners. However, criminological research has yet to fully explore the causes and correlates of website defacement. We consider whether variables derived from routine activity theory can be applied to understanding website defacement. Specifically, using a sample of websites that were targeted by hackers in 2017 across the world, we examine the relationship between a country’s structural characteristics and the frequency of website defacement reported for the country. We find that website defacements are less likely to occur in the presence of capable guardianship (strong military presence) and more likely to occur when certain measures of target suitability are present. Additionally, using hackers’ self-reported valuations of potential targets, we separate defacements into two groups, and examine whether websites targeted for political reasons have different correlates than websites targeted for recreational reasons. Findings reveal that recreational defacements are deterred by capable guardianship (strong military presence) and are influenced by certain measures of target suitability while political defacements are not